University politics under the impact of societal transformation and global processes : South Africa and the case of Stellenbosch University, 1990-2010 - Baumert, Stefanie Christine (Stellenbosch : Stellenbosch University, 2015)
Thesis (PhD)--Stellenbosch University, 2014.